"Responses to the Chilean law of food labeling and advertising: exploring knowledge, perceptions and behaviors of mothers of young children" - Teresa Correa; Camila Fierro; Marcela Reyes; Francesca R. Dillman Carpentier; Lindsey Smith Taillie; Camila Corvalan (BMC, 2019)
Abstract Background In line with calls for action from international health organizations, Chile implemented in June 2016 a set of regulations to tackle the obesity epidemic. The new regulation includes the mandatory use of front-of-package warning labels on packaged foods/beverages high in energy, sugars, saturated fats and sodium. Additionally, such foods cannot be sold nor offered in daycares/schools and cannot be promoted to children under 14yo. The law is targeted to children; thus, this study examined mothers' understanding, perceptions, and behaviors associated with the regulation one year after its implementation, using a qualitative approach. Methods Nine focus groups of mothers (7-10 people each) of children (2-14yo) were conducted in July 2017 in Santiago-Chile. They were stratified by socioeconomic status (SES) and children's age. Macrocodes were developed by three researchers, combining an iterative process of deductive and inductive thematic analyses. Quotations representing each category were selected. Results Mothers understood the new regulation as a policy to fight child obesity and were aware that products with more labels were less healthy than products with fewer labels. Attention and use of labels in the buying decision-making process ranged from participants who did not pay attention to others who relied on them as a quick shortcut (mostly from middle and upper-SES); many mothers indicated changing their purchase habits only when buying new products. Mothers declared that young children accepted school environment changes while teens/preteens resisted them more. Many mothers agreed that schools have become key promoters of food behavioral change. Mothers were less aware about the food marketing regulations. Mothers declared that they perceived that the regulation was changing the perceptions, attitudes and behaviors toward healthier eating patterns. Conclusion After the first year of implementation, the regulation was well known by mothers of diverse SES and different children ages. The degree of use of warning labels was heterogeneous among participants, but most of them agreed that their children, particularly the youngest have positive attitudes toward the regulation and have become promoters of change in their families. Many mothers also expressed that they perceived an important shift toward healthier eating, which may lead to a change in eating social norms. This information contributes to better understand how regulatory actions may influence people's consumer behaviors.